The New Gold Rush The Riches of Space Beckon! - Pelton, Joseph N.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Copernicus, 2017)
This book captures the most exciting advances in the harnessing of space as a global resource. The authors track the growing number of space businesses and opportunities for investors, and the many possible benefits of spaceplanes, space stations and even space colonies. The authors also discuss the need for more regulatory reform. Companies like Planetary Resources are now forming to find mineral-rich asteroids and bring back new riches to Earth. Solar power satellites in the next few years will start to beam clean energy back to Earth, to meet the growing demands of a still-developing world. Innovative space industries are vital to the survival of modern human life, and the authors demonstrate what can be done to encourage the growing of the "New Space" frontier. From lassoing and then mining asteroids to developing new methods of defending the planet from space hazards and setting up new hotels and adventures for tourists in space, this new industry will have profound effects on Earth, especially on its economy. This book is based on a study of international experts commissioned ahead of the UNISPACE+50 meeting, having distilled the results of this comprehensive fact-finding process into a compact and very readable form. It can serve as an excellent starting point for understanding all the activities underway or planned to make space truly our next frontier.
Preface. - Chapter One: Why This Gold Rush is Different -- Chapter Two: The Space Cornucopia of Jobs, Resources and More -- Chapter Three: The Expanding Use of Space in Communications, Navigation, Remote Sensing and Weather Satellites -- Chapter Four: Commercial Space Transport, On-Orbit Servicing and Manufacturing -- Chapter Five: Solar Power Satellites and Space Mining -- Chapter Six: Space Security, Defense and Weapons -- Chapter Seven: Protecting Earth from Space Junk, Cosmic Hazards and Climate Change -- Chapter Eight: Space Habitats, Space Colonies, and the New Space Economy -- Chapter Nine: Governing the New Space Economy -- Chapter Ten: Policing the Gold Rush in the Skies. Chapter 11: Looking Toward a More Hopeful Global Society. - Appendix. - Glossary. - Index.
Keywords: Engineering; Aerospace engineering; Astronautics; Law of the sea; International law; Aeronautics -- Law and legislation; Industrial Management; Solar system; Technology and Engineering; Aerospace Technology and Astronautics; Law of the Sea, Air and Outer Space; Industrial Management; Space Physics